Novel TTN Variant Causing Salih Myopathy and Coexisting Thyroid Dyshormonogenesis: A Case Report - Yıldız, Mustafa; Ataş, Yavuz; Soğukpınar, Merve; Kaya, Oğuz; Gündüz, Onur Recep; Kırık, Serkan (Wiley, 2026)
[Abstract Not Available]
Keywords: DUOX2; hypotonia; pediatric; TTN